2015
DOI: 10.1016/j.jim.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine release assays for the prediction of therapeutic mAb safety in first-in man trials — Whole blood cytokine release assays are poorly predictive for TGN1412 cytokine storm

Abstract: The therapeutic monoclonal antibody (mAb) TGN1412 (anti-CD28 superagonist) caused near-fatal cytokine release syndrome (CRS) in all six volunteers during a phase-I clinical trial. Several cytokine release assays (CRAs) with reported predictivity for TGN1412-induced CRS have since been developed for the preclinical safety testing of new therapeutic mAbs. The whole blood (WB) CRA is the most widely used, but its sensitivity for TGN1412-like cytokine release was recently criticized. In a comparative study, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 48 publications
1
43
2
Order By: Relevance
“…A significant increase of IL-8, IL-10 and IL-6 can be detected with n = 9, 14, and 28 sample sizes at 90% statistical power after treatment with CD28SA. This was inconsistent with the previous finding by Vessillier et al (2015) that a sample size of at least n = 52 was needed to detect a positive response in whole blood and that IL-8 was not significantly increased by TGN1412. They reported that the background level of IL-8 in WBCA was 2,538 pg/mL with the IgG4 control and 2,474 pg/mL with TGN1412 at 5 μg/mL of treatment (Vessillier et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A significant increase of IL-8, IL-10 and IL-6 can be detected with n = 9, 14, and 28 sample sizes at 90% statistical power after treatment with CD28SA. This was inconsistent with the previous finding by Vessillier et al (2015) that a sample size of at least n = 52 was needed to detect a positive response in whole blood and that IL-8 was not significantly increased by TGN1412. They reported that the background level of IL-8 in WBCA was 2,538 pg/mL with the IgG4 control and 2,474 pg/mL with TGN1412 at 5 μg/mL of treatment (Vessillier et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…This was inconsistent with the previous finding by Vessillier et al (2015) that a sample size of at least n = 52 was needed to detect a positive response in whole blood and that IL-8 was not significantly increased by TGN1412. They reported that the background level of IL-8 in WBCA was 2,538 pg/mL with the IgG4 control and 2,474 pg/mL with TGN1412 at 5 μg/mL of treatment (Vessillier et al, 2015). In the present study, medians of IL-8 measurements were 608 pg/mL when treated with panitumumab at 100 μg/mL and 375 pg/mL with PBS, which significantly increased to 1,270, 1,074, and 2,196 pg/mL when concentrations of CD28SA were 1, 10 and 100 μg/mL, respectively (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some conventional preclinical models (rats and non-human primates) may be relatively insensitive to endotoxin and to developing a cytokine storm. 38 In such cases, supplementing in vivo studies with in vitro assays utilizing human blood should be considered. Another consideration for selecting an animal model is related to the variable sensitivity of animal strains to a particular type of immunotoxicity.…”
Section: Translational Challengesmentioning
confidence: 99%
“…6 However, the use of a superagonistic anti-CD28 antibody may not be realistic because of the many serious side-effects, such as multi-organ failure and near-fatal cytokine release syndrome, which were found in another clinical study. 34 Further studies are necessary to confirm the effects of CD28 modification on LV remodeling after MI and elucidate the detailed mechanism of it.…”
Section: Discussionmentioning
confidence: 99%